2017
DOI: 10.22515/shirkah.v2i3.170
|View full text |Cite
|
Sign up to set email alerts
|

Islamicity Financial Performance Index in Indonesian Islamic Banks

Abstract: This study aims to critically analyze the effect of islamic social reporting, intellectual capital  and  the  sharia supervisory board on islamicity financial performance index of Islamic Banks in Indonesia during 2011-2015. The samples of this study are ten islamic commercial banks that were initially selected by using purposive sampling method. Islamicity financial performance index was used as a measure of financial performance of Islamic  banks  which are consist of profit sharing ratio, zakat performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
4
0
2
Order By: Relevance
“…In consequence, Ibrahim, Wirman, Alrazi, Nor, and Pramono (2004) developed the Islamicity financial performance index as an alternative performance measurement model for Islamic banks. The index includes six different financial performance indicators and is considered to offer reliable performance measurement within the framework of Islamic law (Andraeny & Putri, 2017). Kevser (2021) analyzed the performance of different types of banks in Turkey using 13 different financial performance indicators.…”
Section: Islamic Banks' Financial Performancementioning
confidence: 99%
“…In consequence, Ibrahim, Wirman, Alrazi, Nor, and Pramono (2004) developed the Islamicity financial performance index as an alternative performance measurement model for Islamic banks. The index includes six different financial performance indicators and is considered to offer reliable performance measurement within the framework of Islamic law (Andraeny & Putri, 2017). Kevser (2021) analyzed the performance of different types of banks in Turkey using 13 different financial performance indicators.…”
Section: Islamic Banks' Financial Performancementioning
confidence: 99%
“…Untuk memperoleh kepercayaan dari stakeholders perkembangan Bank Syariah harus disertai dengan perkembangan kinerja yang baik. Penilaian pada kinerja Bank Syariah harus sesuai dengan prinsip -prinsip syariah [11]. Kinerja Bank Syariah dapat diukur dengan menggunakan islamicity performance index yang dapat diproksi dengan profit sharing ratio [12].…”
Section: Pendahuluanunclassified
“…Pengukuran kinerja menggunakan islamicity performance index tidak hanya melihat dari sisi materialitas saja, tetapi juga dari sisi spiritual. Berdasarkan islamicity performance index, kinerja perbankan syariah diukur berdasarkan prinsip -prinsip syariah [11], [12], [14], [21]. Hameed et al, (2004) telah mengembangkan suatu indeks yang dapat digunakan untuk melakukan pengukuran kinerja perbankan syariah yang sesuai dengan sifat umum dari bank syariah itu sendiri.…”
Section: Islamicity Performance Indexunclassified
“…On the perspective of sustainability balanced scorecard theory, an organization is assessed if its performance depends on financial or nonfinancial sources. Research has indicated that an organization's transparency and accountability are seen not only by financial statements but also by social responsibility (Ahmad et al, 2018;Andraeny & Putri, 2017); as a result, many organizations use their social accountability reports as a way to improve their credibility and preserve its reputation (Sidik & Reskino, 2016). Hence, this study aims to explore the possible synchronization between BAN-PT policy and the theory of sustainability balanced scorecard.…”
Section: Introductionmentioning
confidence: 99%